A theorem of variational inclusion problems and various nonlinear mappings. Issue 7 (19th May 2018) - Khuangsatung, W.; Kangtunyakarn, A.
ABSTRACT: In this paper, we prove a strong convergence theorem for finding a common element of the set of fixed points of a finite family of nonexpansive mappings and the set of solutions of a finite family of variational inclusion problems in Hilbert spaces. Moreover, we utilize our main result to fixed point problems of various nonlinear mappings and the set of solutions of variational inclusion problems.